The Power of Peer Evaluation: Rethinking Pedagogy in L2 Conversation Courses - Massery, Laurie A. (Nouvelle Revue Synergies Canada, 2016)
Research examining the effectiveness of using peer evaluation as a pedagogical tool in higher education is quickly emerging. Perceptions of such assessments, however, continue to vary among students and educators alike. This paper serves as a review of recent studies that center on peer evaluation, and highlights the positive and negative aspects of such assessments. Following a discussion of current investigations, researchers’ collective findings are aligned with the parameters outlined in the CRGG-C framework, an infrastructure that is designed to capitalize on the benefits of peer evaluation (see Massery 2013), while also addressing some of the negative characteristics identified in the literature.